(3OhQ GdbGVj GdeOfj aj EfTGA GdbGYOI GdbGfhfjI (B/ s - (3CMeO GdZQjH THd GdHfGs; (3CSGeI CMeO Thbj GdedjLj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JfGhdJ GdOQGSI ehVhYjf GdChd gh HjGf WHjYI hfWGb GdhXjaI GdbVGFjI heG EPG cGfJ Jba HGdbGVj YfO eLQO GdJWHjb GdBdj ddbhGYO GdbGfhfjI GdebQQI(B: (3Ce CfgG JJYOi Pdc Edi EfTGA hUfY bhGYO eSJMOKI(B: (3hGdKGfj gh JMOjO GdeUGOQ GdQSejI ddbGYOI GdbGfhfjI heG EPG cGfJ JbJUQ Ydi GdJTQjY hGdYQa Ce CfgG JeJO dJTed GdeHGOF GdbVGFjI hHGNJUGQ aEf GdfbWI GdJj SfJfGhdgG HHMKfG JYJHQ ef GdfbGW GdYedjI GdgGeI LOnG CdG hgj GdJSHjH GdbVGFj ddCMcGe GdeOfjI heOi SdWI GdbGVj aj UfY GdbhGYO GdbGfhfjI hJbJVj OQGSI OhQ GdbGVj aj UfY GdbhGYO GdbGfhfjI Cf fYQV deOi SdWI GdbGVj aj UfY GdbGYOI GdJj jaUd Ydi CSGSgG aj efGRYI eYjfI eYQhVI Ydjg MjfeG dG JSYag GdeUGOQ GdQSejI GdbGFeI aj Md Jdc GdefGRYI(B.s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2017s
(3HHdjhLQGajG(B: (3UaMGJ (B306-324s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3eHOC MjGO GdbGVjs; (3OhQ GdbGVj aj GdNUheI GdeOfjIs; (3fXGe GdShGHb GdbVGFjIs; (3OhQ GdbGVj aj GfTGA GdbGYOI GdbGfhfjIs; (3OhQ GdbGVj GdeOfj aj GfTGA GdbGYOI GdbGfhfjI aj GdbGfhf GdeUQjs; (3cjajI GONGd fXGe GdShGHb GdbVGFjI aj GdfXGe GdbVGFj GdeUQjs; (3GdbVGA eUOQ QSej ddbGfhfs; (3eHOC GdeSGhGI GdaYdjI ddCaQGO GeGe GdbGfhfs; (3fXQjI ceGd GdJTQjYs; (3fXQjI GdfbU aj GdJTQjYs; (3OhQ eMceI GdfbV aj fXGe GdShGHb GdbVGFjIs; (3GdbhI GdedReI ddbhGYO GdbVGFjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes